Kualitas Kinerja Guru Ditinjau dari Pengaruh Inservice Training - Tri Novita Sari; Syarwani Ahmad; Rohana Rohana (Journal on Education, 2023)
The purpose of this research is to find out and analyze how inservice training has an influence on improving the quality of teacher performance. This research uses quantitative methods and is included in survey research. Data collection techniques in this study were through the dissemination of questionnaires. The sample used in this study was 88 teachers of Madrasah Tsanawiyah in East Prabumulih District. Based on the findings of the study, it shows that inservice training has an influence on improving the quality of teacher performance. Research related to inservice training has never been studied before at the Madrasah Tsanawiyah in Prabumulih City. In addition, the novelty in this study is related to inservice training research conducted after the Covid 19 pandemic. This research contributed to the Head of Madrasah, Islamic Education of the Ministry of Religious Affairs of the Republic of Indonesia, and Teachers.